THE MYTHS AND REALITIES OF BAYESIAN CHRONOLOGICAL MODELING REVEALED – ERRATUM. Issue 2 (10th April 2018) - Hamilton, W. Derek; Krus, Anthony M.
Abstract : The originally published version of this article (Hamilton and Krus, 2017) listed the incorrect article type. The correct article type for this article is "Forum."